Association between level of knowledge gained, confidence, motivation and flexibility on types of learning for bedside teaching among clinical students in four Malaysian medical schools during COVID-19 pandemic - Zainal Maaruf, Kamilia; Ngio, Wei Kiat; Balakrishnan, Koustubak; Mohamad Zainal, Nurul Hayati; Omar, Norsuhana; Ku Mohd Noor, Ku Mastura; Wahid, Hanan Hamimi; Mohd Nor, Nurul Huda (UPM Press, 2022)
Introduction: With the arise of the COVID-19 pandemic, higher institutions are forced to change the method of delivery for bedside teaching sessions from face-to-face to online learning. However, online learning was found not effective in delivering practical knowledge and skills to students. Hence, the objective of this study was to determine the association between level of knowledge gained, confidence, motivation and flexibility on types of learning for bedside teaching sessions among clinical students in four Malaysian medical schools during COVID-19 pandemic. Methods: A cross-sectional study involving medical students from Universiti Putra Malaysia (UPM), Universiti Sains Islam Malaysia (USIM), Universiti Islam Antarabangsa (UIA) and Universiti Sains Malaysia (USM) were conducted from 1st March 2021 until 6th June 2021. An online questionnaire was distributed and it consisted of 5 sections which cover sociodemographic information, level of knowledge gained, confidence, motivation, and flexibility from bedside teaching session. The data was analysed by using SPSS software program. Results: There is a significant association between the level of knowledge gained, level of confidence, level of motivation and level of flexibility with the type of learning (online or face-to-face) during bedside teaching sessions. Results revealed that students gained a higher level of knowledge (84.9%), higher level of confidence in physical examination (93.3%), higher motivation (82.2%) and higher flexibility (64.1%) during face-to-face bedside teaching sessions compared to online learning. Conclusion: Most of the medical students in four Malaysian medical schools prefer face-to-face learning compared to online learning for bedside teaching sessions.